2012
DOI: 10.1029/2011jb008811
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear estimation of geometric parameters in FEMs of volcano deformation: Integrating tomography models and geodetic data for Okmok volcano, Alaska

Abstract: [1] The internal structure, loading processes, and effective boundary conditions of a volcano control the deformation observed at the Earth's surface. Using finite element models (FEMs), we simulate the response due to a pressurized magma chamber embedded in a domain having a distribution of elastic material properties. We present the Pinned Mesh Perturbation method (PMP) to automate the mesh generation process in response to perturbations of the position of a simulated magma chamber within an FEM domain. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 62 publications
1
63
0
Order By: Relevance
“…Our analysis indicates that the source location responsible for surface deformation at Okmok during 2008-2014 is very close to-effectively the same as-that active before, during, and after the 1997 and 2008 eruptions [1,10,11,16,[18][19][20]42]. Additionally, similar to deformation trends during 1992-2008, the source strength varied over time during [2008][2009][2010][2011][2012][2013][2014], reflecting changes in the rate of supply to the shallow magma storage zone beneath the volcano.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis indicates that the source location responsible for surface deformation at Okmok during 2008-2014 is very close to-effectively the same as-that active before, during, and after the 1997 and 2008 eruptions [1,10,11,16,[18][19][20]42]. Additionally, similar to deformation trends during 1992-2008, the source strength varied over time during [2008][2009][2010][2011][2012][2013][2014], reflecting changes in the rate of supply to the shallow magma storage zone beneath the volcano.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have results spanning 2011-2014 from TerraSAR-X track 93, we did not include these in modeling of source geometry because of the presence of numerous unwrapping errors. Deformation at Okmok has been modeled using a point source within a homogenous isotropic elastic half-space [17] in previous studies e.g., [1,9,10,16,18,28,30,42]. Lu et al [18] concluded that the synthetic interferograms for the best fit Mogi source are indistinguishable from those for the best fit prolate spherical sources; therefore, the Mogi [17] source is employed in the current analysis for computational simplicity.…”
Section: Deformation Modelling and Analysismentioning
confidence: 99%
“…Previous studies of Okmok demonstrated that models simulating a variable (heterogeneous) distribution of material properties, such as the existence of a caldera filled with weak materials, as determined from seismic tomography models, will lead to estimates of source depths that are significantly deeper than estimates from models having a uniform (homogeneous) distribution of material properties. This result is due to a focusing of the strain within the weak caldera materials [ Masterlark , ; Masterlark et al , , , ]. The purpose of this study is to quantify how deformation source parameters estimated from inverse analyses of geodetic data are influenced by uncertainties in the seismic tomography model.…”
Section: Introductionmentioning
confidence: 99%
“…Note that shear wave velocities vary in both horizontal and vertical directions. Modified from Masterlark et al [].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the analytical source models used to invert the ground deformation data are characterized by being flat Earth models that assume a simple pressure source in a homogeneous, isotropic, elastic half-space. Heterogeneities of the crust, in both lithology and temperature for example, affect the deformation signal observed in the surface (Masterlark et al, 2012); however this information is not available for use in this study. Despite their limitations, the elastic half-space models are widely used primarily because of the simplicity of the equations, the good approximation of the sources obtained, and the rapid processing times, making these A C C E P T E D M A N U S C R I P T 32 models useful for near-real time volcano monitoring (Lisowski, 2007).…”
Section: Our Results Indicate That Six Post-eruption Intrusions Have mentioning
confidence: 76%